Surgical prescription opioid trajectories among state Medicaid enrollees - McCauley, Jenna L.; Ward, Ralph C.; Taber, David J.; Basco, Jr, William T.; Gebregziabher, Mulugeta; Reitman , Charles; Moran, William P.; Cina, Robert A.; Lockett, Mark A.; Ball, Sarah J. (Journal of Opioid Management, 2023)
Objective: The objective of this study was to evaluate opioid use trajectories among a sample of 10,138 Medicaid patients receiving one of six index surgeries: lumbar spine, total knee arthroplasty, cholecystectomy, appendectomy, colon resection, and tonsillectomy. Design: Retrospective cohort. Setting: Administrative claims data. Patients and participants: Patients, aged 13 years and older, with 15-month continuous Medicaid eligibility surrounding index surgery, were selected from single-state Medicaid medical and pharmacy claims data for surgeries performed between 2014 and 2017. Interventions: None. Main outcome measures: Baseline comorbidities and presurgery opioid use were assessed in the 6 months prior to admission, and patients' opioid use was followed for 9 months post-discharge. Generalized linear model with log link and Poisson distribution was used to determine risk of chronic opioid use for all risk factors. Group-based trajectory models identified groups of patients with similar opioid use trajectories over the 15-month study period. Results: More than one in three (37.7 percent) patients were post-surgery chronic opioid users, defined as the dichotomous outcome of filling an opioid prescription 90 or more days after surgery. Key variables associated with chronic post-surgery opioid use include presurgery opioid use, 30-day post-surgery opioid use, and comorbidities. Latent trajectory modeling grouped patients into six distinct opioid use trajectories. Associates of trajectory group membership are reported. Conclusions: Findings support the importance of surgeons setting realistic patient expectations for post-surgical opioid use, as well as the importance of coordination of post-surgical care among patients failing to fully taper off opioids within 1-3 months of surgery.